2012
DOI: 10.1093/annonc/mds113
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and cancer risk: a quantitative review to 2011

Abstract: Observational studies indicate a beneficial role of aspirin on colorectal and other digestive tract cancers; modest risk reductions were also observed for breast and prostate cancer. Results are, however, heterogeneous across studies and dose-risk and duration-risk relationships are still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
233
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 101 publications
22
233
1
2
Order By: Relevance
“…Our findings of the EP2 expression in TAFs in the mesenchyme are consistent with our previous finding that EP2 was expressed in stromal region in Apc D716 mice and Ptger2 deficiency suppressed intestinal polyp formation (43). Furthermore, several studies reported expression of EP2 in various types of cancers (44)(45)(46) and aspirin lowers the risk of solid tumors other than colorectal cancer (4,5). It is interesting to test how widely the EP2 actions we found here operate in microenvironment of cancers other than colorectal cancer.…”
Section: Ly-6gsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of the EP2 expression in TAFs in the mesenchyme are consistent with our previous finding that EP2 was expressed in stromal region in Apc D716 mice and Ptger2 deficiency suppressed intestinal polyp formation (43). Furthermore, several studies reported expression of EP2 in various types of cancers (44)(45)(46) and aspirin lowers the risk of solid tumors other than colorectal cancer (4,5). It is interesting to test how widely the EP2 actions we found here operate in microenvironment of cancers other than colorectal cancer.…”
Section: Ly-6gsupporting
confidence: 91%
“…One major risk factor of colorectal cancer is inflammatory bowel diseases such as ulcerative colitis (2), indicating that the pathogenesis of colorectal cancer is closely associated with inflammatory responses in the colon, and that manipulation of inflammation might prevent colorectal cancer development. In fact, it is well known that the use of aspirin or other NSAIDs is associated with reduction of risk of colorectal cancer (3)(4)(5). NSAIDs, including aspirin, exert their effects by inhibiting COX, an enzyme initiating prostaglandin (PG) biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin has been reported to prevent carcinogenesis of colorectal cancer in Apc Min/þ mice and prevent 44% tumor formation at a dosage of 200 mg/kg through attenuating inflammation (31,32). However, its clinical use for chemoprevention is prohibited due to a significant incidence of gastrointestinal upset and bleeding.…”
Section: Clin Cancer Res; 22(16) August 15 2016mentioning
confidence: 99%
“…On the basis of well-established associations with colorectal cancer risk (8)(9)(10)25), the following predictors were selected: age, BMI, sex, prevalent diabetes, previous colorectal cancer screening, first-degree relative with colorectal cancer, aspirin use, smoking status (never, former, and current), alcohol intake, cereal consumption and wholegrain bread as markers of dietary fiber intake, intake of vegetables, fruits, red meat and processed meat, and vigorous physical activity.…”
Section: Model Developmentmentioning
confidence: 99%